Investigating the anti-cancer activity of cardanol a component of cashew nut shell liquid in oral cancer using in silico analysis - Vishal Jadhav, Anuj Maini, Vaibhav Sunil Ladke (Journal of Applied Pharmaceutical Science, 2025)
There is a significant concentration of bioactive substances in the cashew plant, which is known scientifically as Anacardium occidentale L. These compounds, which are primarily found in the spongy shells of cashew nuts, include phenolic lipids. The liquid that is taken from the shell of the cashew nut contains a lot of cardanol, which is a chemical that has many different applications, the most important of which is that it is a versatile building block that can be used in a variety of different sectors. In addition to their application in industry, cashews and the bioactive components that they contain are well-known for their important biological impacts. In this work, the anticancer potential of cardanol, which is a primary component of cashew nut shell liquid, is evaluated through the use of in silico analysis. This analysis is essential for determining the principal gene targets and cellular signaling pathways that are affected by cardanol in the setting of oral cancer. During the research, 23 genes were discovered to be involved in a wide range of biological processes. These processes include cell migration, proliferation, apoptosis regulation, PI3K-AKT pathway regulation, and cell cycle control. The genes PIK3CA, CCND1, MMP1, and MTOR were the ones that were implicated in the top 10 pathways the most frequently. These genes are all closely related to the PI3K signaling pathway, which suggests that this system may be essential for Cardanol’s potential therapeutic effects in treating oral cancer. Cardanol has been shown to have a substantial anti-proliferative effect on oral cancer, which indicates that it has the potential to be used as a therapeutic agent, according to the findings of the in-silico assessment. These findings may contribute to developing oral cancer treatments that are more effective and suited to the patient’s specific needs, ultimately resulting in improved treatment outcomes.
Keywords: Anacardium occidentale L. cardanol, oral cancer, anti-cancer activity, in-silico analysis, cashew nut shell liquid (CNSL), network pharmacology